An Evaluation of River Health for the Weihe River in Shaanxi Province, China. (4th October 2015) - Song, Jinxi; Cheng, Dandong; Li, Qi; He, Xingjun; Long, Yongqing; Zhang, Bo
Abstract : Excessive socioeconomic activities in the Weihe River region have caused severe ecosystem degradation, and the call for the recovery and maintenance of the river health has drawn great attention. Based on the connotation of river health, previous research findings, and status quo of the Weihe River ecosystem, in this study, we developed a novel health evaluation index system to quantitatively determine the health of the Weihe River in Shaanxi Province. The river in the study area was divided into five reaches based on the five hydrological gauging stations, and appropriate evaluation indices for each river section were selected according to the ecological environmental functions of that section. A hybrid approach integrating analytic hierarchy process (AHP) and a fuzzy synthetic evaluation method was applied to measure the river health. The results show that Linjiancun-Weijiabao reach and Weijiabao-Xianyang reach are in the "moderate" level of health and Lintong-Huaxian reach and downstream of Huaxian reach are in the "poor" health rating, whereas Xianyang-Lintong reach is in the "sick" rating. Moreover, the most sensitive factors were determined, respectively, for each reach from upper stream to lower stream in the study area.